2018
DOI: 10.1136/bjophthalmol-2017-311475
|View full text |Cite
|
Sign up to set email alerts
|

Changes in retinal ischaemic index correlate with recalcitrant macular oedema in retinal vein occlusion: WAVE study

Abstract: The severity of ME was correlated with the ISIs of the entire retina and the PMA. The reduction in ME was correlated with the reduction in ISI of the entire retina as well as the ISIs for the NPA and PMA following TRP. The role of TRP, particularly to these regions (NPA, PMA), warrants further investigation in recalcitrant RVO-associated ME.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 26 publications
(10 reference statements)
2
22
0
1
Order By: Relevance
“…Retinal thinning due to macular ischemia could also be involved in the decrease in CRT. As previously shown, there may be a significant association between the resolution of retinal exudation and that of retinal nonperfusion 21,22 , because retinal perfusion could be the source of exudation. Inclusion of patients with severe CRVO in this study may be a reason for the smaller number of anti-VEGF injections relative to the number in other clinical trials [9][10][11][12][13][14][15] .…”
Section: Discussionmentioning
confidence: 91%
“…Retinal thinning due to macular ischemia could also be involved in the decrease in CRT. As previously shown, there may be a significant association between the resolution of retinal exudation and that of retinal nonperfusion 21,22 , because retinal perfusion could be the source of exudation. Inclusion of patients with severe CRVO in this study may be a reason for the smaller number of anti-VEGF injections relative to the number in other clinical trials [9][10][11][12][13][14][15] .…”
Section: Discussionmentioning
confidence: 91%
“…Of note, CMT and the levels of cytokines showed significant correlation with ischemia in the PMR and NPR. Kwon et al 18 also demonstrated that in patients with RVO and recurrent ME, the severity of ME was correlated only with ISI of PMR and the reduction in ME was correlated with the reduction in ISI in PMR and NPR following targeted retinal photocoagulation (TRP). Taken together, both our study and that of Kwon et al would appear to support the overall contention that ischemia closer to the macula (and not the far periphery) is most relevant to cytokine production and development of ME 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…51,52 Nonetheless, it may result in reduced ischemic indices in the perimacular and near-peripheral areas of the retina and a subsequent reduction in CME, indicating a need for further studies to elucidate the role and parameters of TRP in treating RVO. 43…”
Section: Clinical Utility Of Widefield Imagingmentioning
confidence: 99%